Fiber-Based Compensation of IXPM-Induced Timing Jitter - Striegler, Arne; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2004)
We derive from an analytical approach conditions to cancel out timing jitter by balancing intra channel effects in subsequent link sections. In numerical simulations we proof the applicability of a fiber based compensating structure at 40Gbit/s. © 2003 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.fiberb